Optimization of piezoelectric properties for [001](c) poled 0.94Pb(Zn(1∕3)Nb(2∕3))O(3)–0.06PbTiO(3) single crystals - Xiang, Yang (American Institute of Physics, 2010)
The piezoelectric properties of [001](c) poled 0.94Pb(Zn(1∕3)Nb(2∕3))O(3)–0.06PbTiO(3) single crystals were greatly enhanced by controlling their domain configurations. Contrary to the interpretation of charged domain walls being the main contributor to the piezoelectric enhancement, we found that smaller domain size and more neutral domain walls were the main contributors for the piezoelectric enhancement of these multidomain crystals. The properties of 109° neutral domain walls in 0.94Pb(Zn(1∕3)Nb(2∕3))O(3)–0.06PbTiO(3) single crystals were extracted by using a piezoelectric domain wall model.